Impact of Active and Reactive Current Injections of Utility-Scale PV Generators during Low-Voltage Ride-Through - Bakar M.H.A.; Tan N.M.L.; Ramasamy A.K.; Ridzal Othman M.; Ariffin I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Energy resources; Grid codes; large-scale solar; Low-voltage ride-through; Reactive currents; Voltage sags; Energy management